2007
DOI: 10.1161/atvbaha.107.147868
|View full text |Cite
|
Sign up to set email alerts
|

Role of Osteoprotegerin in Arterial Calcification

Abstract: Objectives-Enhanced osteoclastogenesis, increased bone resorption, and osteoporosis have been reported in osteoprotegerin-deficient (OPG (Ϫ/Ϫ)) mice. OPG (Ϫ/Ϫ) mice available in Japan usually do not show vascular calcification. We have found that arterial calcification can be quickly induced by a simple procedure in OPG (Ϫ/Ϫ) mice. Methods and Results-Male OPG (Ϫ/Ϫ), OPG (ϩ/Ϫ), and OPG (ϩ/ϩ) mice were fed a high phosphate diet from 6 to 10 weeks after birth, and then 1␣,25-dihydroxyvitamin D3 (calcitriol) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 42 publications
3
52
0
1
Order By: Relevance
“…110 OPG was shown to inhibit ALP activity in aortic tissue and prevent the progression of medial layer vascular calcification. 111 Similar results were observed in the diabetic LdlrϪ/Ϫ mouse model, showing again OPG administration diminishes vascular calcium accumulation, potentially through immunomodulatory actions upon dietinduced low-grade mural inflammation. 112 Although little is known about the direct effect of OPG on VSMCs, it is important to understand further its role in osteogenesis and its involvement in the inflammatory response, which is important for the osteoblastic differentiation of VSMCs.…”
Section: Osteopontinsupporting
confidence: 66%
“…110 OPG was shown to inhibit ALP activity in aortic tissue and prevent the progression of medial layer vascular calcification. 111 Similar results were observed in the diabetic LdlrϪ/Ϫ mouse model, showing again OPG administration diminishes vascular calcium accumulation, potentially through immunomodulatory actions upon dietinduced low-grade mural inflammation. 112 Although little is known about the direct effect of OPG on VSMCs, it is important to understand further its role in osteogenesis and its involvement in the inflammatory response, which is important for the osteoblastic differentiation of VSMCs.…”
Section: Osteopontinsupporting
confidence: 66%
“…In this context, the use of either recombinant OPG or a monoclonal antibody against RANKL has been very powerful at alleviating bone erosion in the above mentioned diseases [49,[51][52][53][54][55]. Moreover, recent studies have also shown that the OPG/RANKL ratio plays an important role in controlling vascular calcification [56][57][58][59]: a low OPG/RANKL ratio was correlated with increased vascular smooth muscle cell calcification.…”
Section: Discussionmentioning
confidence: 99%
“…14 These findings are in further agreement with the frequent arterial dissection and rupture in mouse models with aortic vascular calcification. 15,16 Thus, vascular calcification introduces compliance mismatch that can promote mechanical failure due to stress concentration at the interfaces of calcium deposits with softer plaque components.…”
Section: Clinical Impact Of Arterial Calcificationmentioning
confidence: 99%